Virtualisation : the impact of the technology on the financial services sector and the global trends. - Lim, Chye Soon. (2008)
This research report examines the development towards the adoption of virtualisation in the financial sector. It provides a systematic documentation of the migration of financial institutions away from traditional distribution channels. Viewing the electronic channels as a form of new innovation, the authors applied the Virtual Financial Services (VFS). Model and other theories to support their findings.